Synthesis and biological evaluation of an 111In-labeled exendin-4 derivative as a single-photon emission computed tomography probe for imaging pancreatic β-cells. Issue 20 (15th October 2017) - Kimura, Hiroyuki; Fujita, Naotaka; Kanbe, Kaori; Matsuda, Hirokazu; Watanabe, Hiroyuki; Arimitsu, Kenji; Fujimoto, Hiroyuki; Hamamatsu, Keita; Yagi, Yusuke; Ono, Masahiro; Inagaki, Nobuya; Saji, Hideo
Graphical abstract: Abstract: A non-invasive method of pancreatic β-cell mass measurement is needed to enhance our understanding of the pathogenesis of diabetes, facilitate the early diagnosis of this disease, and promote the development of novel therapeutics. Here, we described the synthesis of a novel indium-111 ( 111 In) exendin-4 derivative, [Lys 12 (In-BnDTPA-Ahx)]exendin-4, through a process involving isothiocyanate-benzyl-DTPA (BnDTPA) and 6-aminohexanoic acid (Ahx) attached to an ɛ-amino group at the lysine-12 residue. We further evaluated the potential use of this derivative as a SPECT probe for pancreatic β-cell imaging. An in vitro binding assay revealed that [Lys 12 ( nat In-BnDTPA-Ahx)]exendin-4 has a high affinity for GLP-1 receptors (IC50  = 0.43 nM). In biodistribution experiments involving normal mice, high [Lys 12 ( 111 In-BnDTPA-Ahx)]exendin-4 uptake was observed in the pancreas (21.8  ±  4.0 %ID/g) and was maintained for 2 h after injection. Pre-injection of excess exendin(9−39) markedly reduced the pancreatic uptake of [Lys 12 ( 111 In-BnDTPA-Ahx)]exendin-4 (95.2%), indicating that the uptake of this tracer is specific and mediated by GLP-1 receptors. Ex vivo autoradiography experiments involving pancreatic sections from MIP-GFP mice confirmed the accumulation of [Lys 12 ( 111 In-BnDTPA-Ahx)]exendin-4 in pancreatic β-cells. Finally, in mice, [Lys 12 ( 111 In-BnDTPA-Ahx)]exendin-4 SPECT/CT yielded clear images of the pancreas at 30 min post-injection. In conclusion, SPECT with [Lys 12 ( 111 In-BnDTPA-Ahx)]exendin-4 enables to visualize β-cells in vivo non-invasively.